The Effect of Bank Heterogeneity on the Interest Rate Channel in Lebanon - Ali Awdeh; Zouhour Jomaa; Mohamad Kassem (Journal of Central Banking Theory and Practice, 2020)
The effect of bank heterogeneity on the transmission of monetary policy is capturing an increasing attention, and the debate on how bank specific characteristics may determine their reaction to monetary actions is mounting. This paper participates in this flow of research by studying the reaction of 40 banks operating in Lebanon between 1994 and 2017, to a change in lending interest rate, taking into consideration: size, market power, capitalisation, credit risk, and liquidity. The empirical results show that the impact of a change in interest rate on loan supply depends on bank market power and bank liquidity only. Consequently, interest rate channel in Lebanon operates through banks with high market power and banks with high liquidity stocks.
Keywords: E51; E52; E58; 330; Monetary policy; Interest rate channel; Panel data econometrics.